MELACAK KESULITAN ANAK SAAT BELAJAR PERSPEKTIF PSIKOLOGI - M. Syukri Azwar Lubis (STIT Al-Ittihadiyah Labuhanbatu Utara, 2019)
a study of children berkesulitan learning is part of the children in need special that has the study of differences and diversity. A boy who could berkelainan have special talents or difficulties in terms of seeing, hearing, speaking, thinking, moving or socialize. A study of children berkelainan is also the study of equations. Berkelainan a child is not different with children in General in all things. Perhaps more similarities in terms of characteristics, needs, and how to learn rather than differences among children berkelainan and not berkelainan. For purposes of the education of children berkelainan was defined as those who are in need of special education needs and related services when they realized the ability or will of their full potential. However, we must remember that they are very different in their characteristics and needs. On the discussion of the next chapter will be explained more about the learning difficulties in the face by a child.